نظام الأكوابونيك كوسيلة لتطوير الزراعة في المناطق الصحراوية - بكاري ،نورالدين; عوادي ،مصطفى (جامعة الوادي University of Eloued, 2025)
إن نجاح وازدهار القطاع الزراعي مرهون بالأساس بتوفر الماء وطرق استعماله كمورد يتميز بالندرة، حيث سعت معظم الدول إلى البحث عن أفضل وأحسن الطرق المؤدية لتحقيق إنتاجية أعلى وتقليص استعمال الماء بالخصوص في الأراضي الصحراوية. نهدف من خلال هذا البحث إلى محاولة معرفة واقع استعمال نظام الاكوابونيك في صحراء الجزائر ومدى قدرة هذا النظام على رفع الإنتاج الزراعي في المناطق الصحراوية وكذلك توضيح جدوى تبني نظام الأكوابونيك من أجل زيادة كفاءة المياه والزراعة ، وتوصلت الدراسة إلى وجود تأثير ايجابي لنظام الاكوابونيك على تطوير الزراعة الصحراوية من خلال زيادة الانتاج وتقليل استهلاك المياه وكذلك استعمال مصادر الطاقة البديلة. The success and prosperity of the agricultural sector depends primarily on the availability of water and the methods of utilizing them, a scarce resource. Most countries have sought to find the best and most efficient methods to achieve higher productivity and reduce Water use, especially in desert lands. Through this research, we aim to try to know the reality of using the aquaponics system in the Algerian desert and the extent of the ability of this system to increase agricultural production in desert areas, as well as to clarify the feasibility of adopting the aquaponics system in order to increase the efficiency of water and agriculture. The study concluded that there is a positive impact of the aquaponics system on developing desert agriculture through increasing production and reducing water consumption, as well as using alternative energy sources
Aquaponics as a means of developing agriculture in desert areas
Keywords: الاكوابونيك; الزراعة الصحراوية; الإنتاج، المياه; الطاقة البديلة; Aquaponic; the desert agriculture; the production; water; alternative energy